Vzroki in mehanizmi nazadovanja liberalne demokracije v državah članicah EU - Malčič, Matevž (visokošolska dela, 2022)
The early 21st century has seen the return of the spectre of autocratisation in the advanced industrial democracies of Europe and North America. Beyond just a loss of the quality of democracy, the very institutions of liberal democracy – with their horizontal accountability and judicial constraints on the executive – are in danger. The rising form of autocratisation, known as executive aggrandisement, is the result of a gradual and electoral-driven process. Its drivers are the four interconnected challenges of anti-political-establishment parties (APEp), affective polarisation, deconsolidation and inequality. Previous studies have addressed and found these drivers’ individual detrimental effects on liberal democracy, but they have never all been tested in a single model. We study their effects using a mixed-method approach. For quantitative causal testing, we use fixed-effects time-series cross-sectional data for the EU-28 from 1990 to 2017. We find that increased support for APEp decreases not only the overall Varieties of Democracy (V-Dem) index of liberal democracy but also its subcomponents. Our models do not show the individual effect of the other challenges when all of them are controlled for. To examine how executive aggrandisement has taken place, we use process tracing and advance a first-of-its-kind process proposal. We test the proposal for the cases of Hungary and Poland from 2010 and 2015, respectively, to 2021. We confirm the central role of APEp, which use their control over personalised parties to enact their will after obtaining the necessary absolute or constitutional parliamentary majority because of polarisation and crisis performance. Having been seen as competent leaders, they can also repeat their successes in subsequent elections, while a divided opposition is unable to present a united front or offer an attractive alternative. Based on our discoveries, we present recommendations on how to improve the study of autocratisation in 21st-century democracies.
Keywords: avtokratizacija; Demokracija; Disertacije; Evropska unija; Madžarska; Politične stranke; politični sistemi; politika; Poljska